Towards 2-μm comb light source based on multiple four-wave mixing in a dual-frequency Brillouin fiber laser - Deroh Moise; Xu Gang; Lucas Erwan; Beugnot Jean-Charles; Maillotte Hervé; Sylvestre Thibaut; Kibler Bertrand (Journal of the European Optical Society-Rapid Publications, 2024)
In this study, we report the generation of multi-wavelength light sources through enhanced four-wave-mixing processes using a straightforward and adaptable dual-frequency Brillouin fiber laser. This passive optical and nonreciprocal cavity is first tested and analyzed with long fiber lengths up to 1 km in the 1.55 μm telecommunication C band and then in the 2-μm waveband. In the latter case, we demonstrate that our fiber cavity enables efficient multiple four-wave mixings, in the continuous-wave regime, which are commonly inaccessible in long silica-fibers due to increased losses. We also report on the tunable repetition rate from tens of GHz to hundreds of GHz, by simply changing the frequency spacing between the two continuous-wave pumps. The coherence limitations of our all-fiber system are discussed, along with the impact of the dispersion regime of the nonlinear fiber that forms the cavity.